Methodology for Developing Transversal Competencies of Future Teachers Based on A Modular Competency Approach - Askarova Barchinoy Abdirahimovna (Scientific Trends, 2025)
This research article examines, from a scientific and analytical perspective, a methodology for developing transversal (general professional) competencies in future teachers based on a modular competency-based approach. The flexible structure, practical focus of modular learning, and the potential for integrating competencies are considered an effective tool for developing transversal skills and qualifications.
Keywords: Modular competency approach, transversal competencies, future teachers, methodology, general professional skills, pedagogical education, competency approach.